1992
DOI: 10.1080/01652176.1992.9694319
|View full text |Cite
|
Sign up to set email alerts
|

Interference of maternal antibodies with the immune response of foals after vaccination against equine influenza

Abstract: SUMMARYThe purpose of the study was twofold First, using two groups of 22 foals each, we investigated the extent to which maternal antibodies interfere with the humoral response against equine influenza. The foals were born to mares that had been vaccinated twice yearly against influenza since 1982. Foals of group I were vaccinated three times at early ages (12 16, and 32 weeks of age), and foals of group II were likewise vaccinated but at later ages (24, 28, and 44 weeks of age). After the first and second va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 9 publications
3
41
1
1
Order By: Relevance
“…Apart from vaccine potency (see below) and strain composition, the timing of vaccination is important and can have an impact on vaccine efficacy. It is well accepted that even low levels of maternal antibodies can interfere with successful immunisation [20,94,96] and determine the proper time of vaccination. The disappearance of these antibodies can be monitored by Haemagglutination Inhibition (HI), Single Radial Haemolyis (SRH) or Enzyme Linked Immunosorbant Assays (ELISA) and the results of several independent studies [20,94,96] have shown that the majority of foals born to vaccinated mares should not be vaccinated before 24 weeks of age.…”
Section: Equine Influenzamentioning
confidence: 99%
“…Apart from vaccine potency (see below) and strain composition, the timing of vaccination is important and can have an impact on vaccine efficacy. It is well accepted that even low levels of maternal antibodies can interfere with successful immunisation [20,94,96] and determine the proper time of vaccination. The disappearance of these antibodies can be monitored by Haemagglutination Inhibition (HI), Single Radial Haemolyis (SRH) or Enzyme Linked Immunosorbant Assays (ELISA) and the results of several independent studies [20,94,96] have shown that the majority of foals born to vaccinated mares should not be vaccinated before 24 weeks of age.…”
Section: Equine Influenzamentioning
confidence: 99%
“…The temptation is to vaccinate elite stock prior to the loss of maternal antibodies to avoid any window of susceptibility. Foals born to mares vaccinated during the gestation period have high levels of maternal antibody within two days of birth [13,61,63]. In contrast to Liu et al [32], who reported that maternal antibody persisted for only a short period, several authors [13,61,63] found that the majority of foals they tested had detectable (HI) antibody titres at three months of age but these had virtually disappeared at six months.…”
Section: Optimising Vaccination Schedulesmentioning
confidence: 68%
“…Foals born to mares vaccinated during the gestation period have high levels of maternal antibody within two days of birth [13,61,63]. In contrast to Liu et al [32], who reported that maternal antibody persisted for only a short period, several authors [13,61,63] found that the majority of foals they tested had detectable (HI) antibody titres at three months of age but these had virtually disappeared at six months. Cullinane et al [13] suggested that not only does vaccination in the face of maternal antibody interfere with the development of active immunity but that repeat vaccination in the face of maternal antibodies may induce tolerance.…”
Section: Optimising Vaccination Schedulesmentioning
confidence: 68%
See 2 more Smart Citations